The Role of Circulating MicroRNAs in Patients with Early-Stage Pancreatic Adenocarcinoma - Eid, Michal; Karousi, Paraskevi; Kunovský, Lumír; Tuček, Štěpán; Brančíková, Dagmar; Kala, Zdeněk; Slabý, Ondřej; Mayer, Jiří; Kontos, Christos K; Trna, Jan (Biomedicines, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is increasing in incidence and is still associated with a high rate of mortality. Only a minority of patients are diagnosed in the early stage. Radical surgery is the only potential curative procedure. However, radicality is reached in 20% of patients operated on. Despite the multidisciplinary approach in resectable tumors, early tumor recurrences are common. Options on how to select optimal candidates for resection remain limited. Nevertheless, accumulating evidence shows an important role of circulating non-coding plasma and serum microRNAs (miRNAs), which physiologically regulate the function of a target protein. miRNAs also play a crucial role in carcinogenesis. In PDAC patients, the expression levels of certain miRNAs vary and may modulate the function of oncogenes or tumor suppressor genes. As they can be detected in a patient's blood, they have the potential to become promising non-invasive diagnostic and prognostic biomarkers. Moreover, they may also serve as markers of chemoresistance. Thus, miRNAs could be useful for early and accurate diagnosis, prognostic stratification, and individual treatment planning. In this review, we summarize the latest findings on miRNAs in PDAC patients, focusing on their potential use in the early stage of the disease.
Keywords: microRNA; early stage; chemoresistance; prognosis; pancreatic cancer; diagnosis